A Conceptual System of Antecedents and Processes in Social Entrepreneurship Opportunity Identification - Vial, Virginie; Richomme-Huet, Katia (Frontiers in Psychology, 2021)
Aiming to complement and ground the theory of social entrepreneurship opportunity identification, we draw from a database of 2,872 entrepreneurs’ life stories with two main objectives. The first is to provide a comprehensive list and categorization of antecedents of opportunity identification in the context of social entrepreneurship. The second is to demonstrate the systemic interconnections between those and build a model of social entrepreneurship opportunity identification. We review the literature and establish a framework of five high-order key antecedents’ areas (context, background, social networks and interactions, affect, and cognitive process). We then proceed to a five-step empirical triangulation methodology mixing computerized and manual content analysis. We thereby identify 42 antecedents nested into 17 first-level items grouped into the five high-order key antecedents’ areas. Our detailed results shed light on a wide array of previously ignored antecedents and provide more precisions about those that had already been documented elsewhere. Finally, we highlight and explain the relationships between the antecedents, show that they constitute an “opportunity growing ground”, and present a full model of social entrepreneurship opportunity identification based on their interconnections. The context of the social entrepreneur combines stable features regarding access to various resources, a strong geographical identity and history, the encounter of several worlds, all condition or are conditioned by his/her social networks and background. This context is also subject to diverse constraints and institutional barriers that can shape the entrepreneur’s background, her/his experiences, as well as his/her affect specificities. This stable context is at some point hit by elements of change that disrupt this stability, triggering chains of reactions between the various antecedents of opportunity identification.